Ribavirin for Hepatitis E Virus Infection After Organ Transplantation: A Large European Retrospective Multicenter Study. (3rd December 2019) - Kamar, Nassim; Abravanel, Florence; Behrendt, Patrick; Hofmann, Jörg; Pageaux, Georges Phillippe; Barbet, Christelle; Moal, Valérie; Couzi, Lionel; Horvatits, Thomas; De Man, Robert A; Cassuto, Elisabeth; Elsharkawy, Ahmed M; et al.
Abstract: Background: Ribavirin is currently recommended for treating chronic hepatitis E virus (HEV) infection. This retrospective European multicenter study aimed to assess the sustained virological response (SVR) in a large cohort of solid organ transplant (SOT) recipients with chronic HEV infection treated with ribavirin monotherapy (N = 255), to identify the predictive factors for SVR, and to evaluate the impact of HEV RNA mutations on virological response. Methods: Data from 255 SOT recipients with chronic HEV infection from 30 European centers were analyzed. Ribavirin was given at the median dose of 600 (range, 29–1200) mg/day (mean, 8.6 ± 3.6 mg/kg/day) for a median duration of 3 (range, 0.25–18) months. Results: After a first course of ribavirin, the SVR rate was 81.2%. It increased to 89.8% when some patients were offered a second course of ribavirin. An increased lymphocyte count at the initiation of therapy was a predictive factor for SVR, while poor hematological tolerance of ribavirin requiring its dose reduction (28%) and blood transfusion (15.7%) were associated with more relapse after ribavirin cessation. Pretreatment HEV polymerase mutations and de novo mutations under ribavirin did not have a negative impact on HEV clearance. Anemia was the main adverse event. Conclusions: This large-scale retrospective study confirms that ribavirin is highly efficient for treating chronic HEV infection in SOT recipients and shows that the predominant HEV RNA polymerase mutations found in this study do not affect the rate of HEV clearance. This large-scale retrospective study that included 255 solid organ transplant recipients confirms that ribavirin is highly efficient for treating chronic hepatitis E virus (HEV) infection and shows that HEV RNA polymerase mutations do not play a role in HEV clearance.